1997
DOI: 10.1038/sj.onc.1200982
|View full text |Cite
|
Sign up to set email alerts
|

A role for the small GTPase Rac in polyomavirus middle-T antigen-mediated activation of the serum response element and in cell transformation

Abstract: The oncogenic proteins encoded by papovaviruses, the tumor antigens, have been extensively used as model systems to study mitogenic signaling and cell transformation. These proteins stimulate cell growth in cultured cells and induce tumors in virus infected or transgenic animals. One of these proteins, polyomavirus middle-T, acts like a constitutively activated tyrosine growth factor receptor. Middle-T recruits several cellular enzymes into a multifunctional complex located at cellular membranes. This results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
4
29
1
1
Order By: Relevance
“…Middle T signaling pathways may not always affect downstream targets in a discrete or exclusive way (33,34). These pathways may intersect, and the manner of their interaction and consequent effects on cell growth are likely to differ in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Middle T signaling pathways may not always affect downstream targets in a discrete or exclusive way (33,34). These pathways may intersect, and the manner of their interaction and consequent effects on cell growth are likely to differ in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, MAPK activation has been shown to be associated with AP-1 activation in other systems (Marra et al, 1995;Urich et al, 1997). Urich et al (1995) have shown that nuclear translocation of MAPKs by MT or serum is dependent on PI3K activity.…”
Section: Mt Binding To P13k Is Necessary For Constitutive Ap-1 Activitymentioning
confidence: 99%
“…This leads to activation upon phosphorylation by a not yet identi®ed cellular kinase, presumably also located at cellular membranes (Alessi et al, 1996). It has also been shown that PI 3-kinase is required for full activation of the Ras/MAPK pathway by middle-T as well as for signaling to serum response factor (Urich et al, 1997). Mutants of middle-T still capable of activating PI 3-kinase, but lacking a binding site for SHC, trigger stimulation of p70 S6-kinase (Dahl et al, 1996) or p21 Rac -mediated transcriptional regulation (Urich et al, 1997).…”
Section: Introductionmentioning
confidence: 99%